PENGARUH KREATIVITAS GURU DALAM PROSES BELAJAR MENGAJAR TERHADAP PRESTASI BELAJAR SISWA DALAM MATA PELAJARAN AKUNTANSI : Survei pada kelas XI IPS di SMA Negeri 1 Cikampek - Iis Pertiwi, - (2011)
The background research is the lower of asses student of accounting subjects, this matter is caused by the lack of student comprehend and master of accounting subjects. The aim of the research is to know the description creativity of teacher in course of learning to teach, the creativity teacher achievement and than the influence creativity teacher in course of learning to teach to student learning achievement. The Method used in this research is survey verifikative method. The population in this research is students of class of XI IPS SMA Negeri 1 Cikampek amounting to 158 students by sample as much 61 students. Creativity Data of teacher in course of learning to teach obtained from result of equate spreading the while learning achievement the students obtained from documentation study. The Analyze data used the correlation analysis constructively program the Microsoft excel 2007. The description creativity of teacher in course of learning to stay teach in the high category and the students learning achievement of class of XI Accounting in Accounting Subjects at the category is the precisely. The result of the indicated research which is the learn creativity in course of learning to teach an effect to learning achievement the students of class of XI Accounting of Accounting Subjects in SMA Negeri 1 Cikampek, the tested and accepted its truth with the belief level 95%. This matter is proved with the value correlation is equal to 0, 68 and also coefficient determination is equal to 46, 24% and the rest is equal to 53, 76% influenced by other; dissimilar factor. The suggestion from this research for example: the expected for the direction school more improving of learning creativity in course of learning to teach, expected by a accounting teacher in SMA Negeri 1 Cikampek more creative in using of method and study media has matching with the matter to be sent.